2012
DOI: 10.1088/0004-637x/756/2/180
|View full text |Cite
|
Sign up to set email alerts
|

THECHANDRAHRC VIEW OF THE SUBARCSECOND STRUCTURES IN THE NUCLEAR REGION OF NGC 1068

Abstract: We have obtained a high spatial resolution X-ray image of the nucleus of NGC 1068 using the High Resolution Camera (HRC-I) on board the Chandra X-ray Observatory, which provides an unprecedented view of the innermost 1 arcsec radius region of this galaxy. The HRC image resolves the narrow-line region into X-ray emission clumps matching bright emission-line clouds in the HST [OIII] λ5007 images and allows comparison with subarcsecondscale radio jet for the first time. Two distinct X-ray knots are revealed at 1.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 38 publications
(79 reference statements)
1
30
0
Order By: Relevance
“…7, for NGC 1386) and is coincident with the extent and morphology of the narrow-line region traced by the [OIII] ionized gas (Capetti et al 1997;Bianchi et al 2006;Wang et al 2012), suggesting that both the diffuse X-ray and the [O III] emission are produced by the same gas photoionized by the nuclear continuum (e.g. Iwasawa et al 2003;Wang et al 2012). The extension of the nuclear 0.3-10 keV band X-ray emission is also comparable to the nuclear warm H2 2.1 × 10 −15 * Predicted H 2 2.12µm fluxes assuming a conservative filling factor of 10%.…”
Section: Source Of the Warm H2 Molecular Gas Emissionmentioning
confidence: 60%
“…7, for NGC 1386) and is coincident with the extent and morphology of the narrow-line region traced by the [OIII] ionized gas (Capetti et al 1997;Bianchi et al 2006;Wang et al 2012), suggesting that both the diffuse X-ray and the [O III] emission are produced by the same gas photoionized by the nuclear continuum (e.g. Iwasawa et al 2003;Wang et al 2012). The extension of the nuclear 0.3-10 keV band X-ray emission is also comparable to the nuclear warm H2 2.1 × 10 −15 * Predicted H 2 2.12µm fluxes assuming a conservative filling factor of 10%.…”
Section: Source Of the Warm H2 Molecular Gas Emissionmentioning
confidence: 60%
“…The filled squares in Figure 7 given in the plot legend, while the values for other parameters are presented in Table 4. 01 line ratio varies from -0.5 2.0 in galaxies with kinetic temperature around 20-30 K (e.g., Cen A, NGC 4945, and NGC 253), to the extreme large values (~-10 40) in galaxies with  -T 80 100 k K, which are well known to harbor "shocked gas" (e.g., NGC 6240 and NGC 1068; Müller Sánchez et al 2009;Wang et al 2012Wang et al , 2014Meijerink et al 2013;Papadopoulos et al 2014). As such, we suggest that the -2 1 12 01 / -1 1 10 01 line ratio can be utilized as a good indicator of "shock condition" where gas is heated to high kinetic temperatures.…”
Section: H 2 O Sledmentioning
confidence: 99%
“…To investigate whether the 2nd AGN scenario is consistent with other observational signatures, we use X-ray and radio data and search for evidence of multiple cores at the central region. Starting with X-ray data, we check the Chandra high-resolution camera (HRC) data of NGC 1068 (Ob-sID: 12705; PI: Fabbiano), which were previously presented by Wang et al (2012) 2012), the Chandra image with the PSF deconvolution resolves another putative X-ray point source at 3.6 NE of the nucleus (∆RA= +2.00 , ∆Dec= +2.75 . The detection of the point source is significant at the >7σ level when we take into account the Poisson noise of the adjacent pixels.…”
Section: Counterpart In Multiwavelength Datamentioning
confidence: 99%
“…To further investigate the origin of the X-ray point source, we measure the [O III]/soft X-ray ratio, which is a tracer of ionization states (Bianchi et al 2006). By investigating the ratio for several X-ray knots in the central region of NGC 1068, Wang et al (2012) reported that a few of them were originated from shocks. Using the same data set and method of Wang et al (2012), we find the ratio of ∼ 8.6 ± 0.86 at the pixel of the X-ray point-source position (i.e., within the extraction area of 0.13 × 0.13 ).…”
Section: Counterpart In Multiwavelength Datamentioning
confidence: 99%
See 1 more Smart Citation